The 6-week postpartum oral glucose tolerance test for women with gestational diabetes: an opportune time for risk assessment and for implementing lifestyle changes. (16th November 2010) - Bird, A; O'Brien, J; Candelier, C
Abstract : National Institute for Health and Clinical Excellence guidelines for 'Diabetes in Pregnancy' recommend women with gestational diabetes (GDM) have a fasting blood glucose (FBG) measurement 6 weeks after delivery as opposed to oral glucose tolerance test (OGTT), a cost saving to the National Health Service without affecting outcomes. Study objectives were to evaluate benefits of a 6-week postpartum OGTT (PP OGTT) over FBG measurements in women with GDM. Between January 2006 and December 2008, 126 out of 137 women with GDM (92%) attended the maternity unit for PP OGTT. A specialist midwife in diabetes wrote to the general practitioners of the 12 non-attenders informing them postpartum screening for diabetes was not performed. The specialist midwife gave advice to all attenders on future pregnancy management and on benefits of weight control, diet and exercise. 24 women screened (19%) had an abnormal OGTT: 16 women (12.7%) persistent impaired glucose regulation and 8 women (6.4%) type 2 diabetes. Women with an abnormal OGTT were seen by a diabetologist or referred back to primary care. GDM is associated with increased risks of developing diabetes in subsequent pregnancies, type 2 diabetes and cardiovascular disease. Adopting long-term lifestyle changes reduces these risks. PP OGTT screening identified 16 young women with persistent impaired glucose regulation who could be offered not only lifestyle advice but also a full cardiovascular risk assessment with appropriate follow-up (2002 NSF for Diabetes) while PP FBG screening would have identified only the eight women with type 2 diabetes. Effective communication pathways between women, secondary and primary care are essential to ensure compliance, long-term follow-up and regular screening.